The Novel Effect of a New Prostacyclin Analogue ZK36374 on the Aggregation of Human Platelets in Whole Blood - Saniabadi, A R; Lowe, G D O; Belch, J J F; Forbes, C D; Prentice, C R M; Barbenel, J C (Thrombosis and Haemostasis, 1983)
Platelet aggregation was studied at 37° C in citrated whole human blood, using the Ultra Flo 100 Whole Blood Platelet Counter. Aggregation was measured as a fall in the number of single platelets following addition of an aggregating agent. At peak aggregation, the fall in the number of platelets induced by ADP (10 μM), collagen (1 μg/ml) or thrombin (0.2 U/ml) was about 90%. When blood was incubated with the prostacyclin- analogue ZK36374, the aggregation responses to ADP, collagen and thrombin were reduced with IC50’S = 0.5, 1.5 and 3 nM respectively and the corresponding IC100’S were: 1, 3 and 12 nM. When ZK36374 was added at peak aggregation, the number of single platelets increased significantly due to disaggregation of preformed platelet aggregates. It is concluded that the present technique represents a rapid, sensitive and more physiological approach for investigating the effects of pharmacological agents on platelet aggregation.
Keywords: Whole blood; Platelet aggregation; Platelet disaggregation; ZK36374; Ultra Flo 100